Perinatal depression screening practices in a large health system: identifying current state and assessing opportunities to provide more equitable care - Sidebottom, Abbey (Arch Womens Ment Health, 2020)
The purpose of this study was to assess the prevalence of prenatal and postpartum depression screening in a large health system and to identify covariates for screening, with a specific focus in understanding disparities in practice. A retrospective cohort of women with deliveries in 2016 was created using electronic health records. Primary outcomes were depression screening during pregnancy and the first 3 months postpartum. Generalized linear mixed models with women nested within clinic were used to determine the effect of maternal and clinical characteristics on depression screening. The sample included 7548 women who received prenatal care at 35 clinics and delivered at 10 hospitals. The postpartum sample included 7059 women who returned within 3 months for a postpartum visit. Of those, 65.1% were screened for depression during pregnancy, and 64.4% were screened postpartum. Clinic site was the strongest predictor of screening, accounting for 23–30% of the variability in screening prevalence. There were no disparities identified with regard to prenatal screening. However, several disparities were identified for postpartum screening. After adjusting for clinic, women who were African American, Asian, and otherwise non-white (Native American, multi-racial) were less likely to be screened postpartum than white women (AOR (CI)’s 0.81 (0.65, 1.01), 0.64 (0.53, 0.77), and 0.44 (0.21, 0.96), respectively). Women insured by Medicaid/Medicare, a proxy for low-income, were less likely to be screened postpartum than women who were privately insured (AOR (CI) 0.78 (0.68, 0.89)). National guidelines support universal depression screening of pregnant and postpartum women. The current study found opportunities for improvement in order to achieve universal screening and to deliver equitable care.